Trial of Optimal Personalised Care After Treatment for Gynaecological cancer (TOPCAT-G): a study protocol for a randomised feasibility trial. Issue 1 (December 2016) - Pye, Kirstie; Totton, Nicola; Stuart, Nicholas; Whitaker, Rhiannon; Morrison, Val; Edwards, Rhiannon; Yeo, Seow; Timmis, Laura; Butterworth, Caryl; Hall, Liz; Rai, Tekendra; Hoare, Zoe; et al.
Abstract Background Gynaecological cancers are diagnosed in over 1000 women in Wales every year. We estimate that this is costing the National Health Service (NHS) in excess of £1 million per annum for routine follow-up appointments alone. Follow-up care is not evidence-based, and there are no definitive guidelines from The National Institute for Health and Care Excellence (NICE) for the type of follow-up that should be delivered. Standard care is to provide a regular medical review of the patient in a hospital-based outpatient clinic for a minimum of 5 years. This study is to evaluate the feasibility of a proposed alternative where the patients are delivered a specialist nurse-led telephone intervention known as Optimal Personalised Care After Treatment for Gynaecological cancer (OPCAT-G), which comprised of a protocol-based patient education, patient empowerment and structured needs assessment. Methods The study will recruit female patients who have completed treatment for cervical, endometrial, epithelial ovarian or vulval cancer within the previous 3 months in Betsi Cadwaladr University Health Board (BCUHB) in North Wales. Following recruitment, participants will be randomised to one of two arms in the trial (standard care or OPCAT-G intervention). The primary outcomes for the trial are patient recruitment and attrition rates, and the secondary outcomes are quality of life, health status and capability, using the EORTC QLQ-C30, EQ-5D-3L and ICECAP-A measures. Additionally, a client service receipt inventory (CSRI) will be collected in order to pilot an economic evaluation. Discussion The results from this feasibility study will be used to inform a fully powered randomised controlled trial to evaluate the difference between standard care and the OPCAT-G intervention. Trial registration ISRCTN45565436 .